2016
DOI: 10.18632/oncotarget.12833
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol induces a favourable shift of anti-tumor immunity in a murine spontaneous model of melanoma

Abstract: In a previous study on a xenograft model of melanoma, we showed that the beta-adrenergic receptor antagonist propranolol inhibits melanoma development by modulating angiogenesis, proliferation and cell survival. Stress hormones can influence tumor development in different ways and norepinephrine was shown to downregulate antitumor immune responses by favoring the accumulation of immunosuppressive cells, impairing the function of lymphocytes. We assessed the effect of propranolol on antitumor immune response in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 66 publications
(69 reference statements)
3
60
0
1
Order By: Relevance
“…We found that the major effect of β-AR signaling blockade by propranolol treatment occurred at the CD8 + T-cell response level. Our findings are consistent with recent studies showing that adrenergic signals impaired the anti-tumor CD8 + T-cell response, a phenomenon that may be reversed by β-blocker treatment (26)(27)(28)36). Interestingly, the inhibition of the CD8 + T-cell response by adrenergic signals is not limited to the tumor setting and has also been shown in the context of infection, such as influenza (37).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the major effect of β-AR signaling blockade by propranolol treatment occurred at the CD8 + T-cell response level. Our findings are consistent with recent studies showing that adrenergic signals impaired the anti-tumor CD8 + T-cell response, a phenomenon that may be reversed by β-blocker treatment (26)(27)(28)36). Interestingly, the inhibition of the CD8 + T-cell response by adrenergic signals is not limited to the tumor setting and has also been shown in the context of infection, such as influenza (37).…”
Section: Discussionsupporting
confidence: 92%
“…We have previously reported that the incidence of a carcinogen-induced tumor model (3-methylcholanthrene; MCA) is reduced in mice housed at 22°C compared to 30°C (14), suggesting that adrenergic signaling likely plays a role in immune surveillance and immune editing. Using a transgenic rat model of melanoma, Wrobel et al (38) found that propranolol also decreased tumor incidence, reduced the number of myeloid cells, and increased the presence of GzmB + CD8 + T cells in tumors at endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results from different studies concur to demonstrate that the effect of propranolol in reducing melanoma progression in mouse xenografts bearing human melanoma cells is dependent on the specific cell type and the experimental conditions (Wrobel and Le Gal, ; Zhou et al ., ; Kuang et al ., ). Finally, in a murine spontaneous model of melanoma, propranolol delays primary tumour growth and metastasis development by decreasing the infiltration of immunosuppressive cells in the tumour micro‐environment (Wrobel et al ., ).…”
Section: β1‐ and β2‐adrenoceptors In Melanoma: Preclinical Data And Mmentioning
confidence: 97%